A COMPARISON BETWEEN NOVEL AND MOVIE VERSION OF NATHANIEL HAWTHORNE'S THE SCARLET LETTER:A STRUCTURAL ANALYSIS - Parikesit, Parikesit (2010)
This study deals with similarities and differences of The Scarlet Letter in the novel and the movie version. This research paper is aimed at analyzing the structural elements in both the novel and the movie version by finding out the similarities and differences between them. The present writer uses the theory of structural elements of novel and movie version. This research paper is conducted by using the following methods. The type of the study is qualitative study that is comparing The Scarlet Letter in the novel and movie version. The type of data is a text and movie scene. The methods of data collection are library research and documentation. The techniques of data analysis are descriptive and comparative. The object of this research is The Scarlet Letter both the novel by Nathaniel Hawthorne and the movie version directed by Roland Joffe. The outcomes of the study as follows: (1) there are similarities and differences between the novel and the movie version. The similarities of both versions lie in characters and characterization, setting of place, plot and diction. The differences found in this comparison lie in the limitation characters and characterization, the point of view, mise-en-scene and editing. (2) The director still keeps some of the certain elements within this film because he wants to show the scene of the original version. (3) The director successfully adapts from the novel versions into a brilliant movie. He can also make the movie not only consumption for teenagers, but also for adults.